Identifying Innovative Reliable Criteria Governing the Selection of Infrastructures Construction Project Delivery Systems - Nouh Meshref Ahmed; Elkasaby E.A.; Wageh Omnia (Open Engineering, 2021)
No doubt that the most vital issues to achieve a great success project are the choice of best suitable project delivery methods. According to the experience of project management staff, the delivery of the project is chosen. However, that leads to similar repetitive issues, for example, exceeding the cost of the project and exceeding the project's schedule, and that's what many projects face. It is difficult to develop the management of the recurring issues of the project because there is no awareness of delivery methods. The efficiency of project implementation is greatly affected by selecting the appropriate delivery method. Fuzzy data at early stages of construction projects leads to the fuzzy decision of selection a suitable type to deliver the project contract. In this study, the main purpose was to determine the comprehensive criteria that significantly influence the selection of infrastructures construction project delivery systems. These criteria will aid decision making process more comprehensive and effective innovation tool to choose the reliable Infrastructures Project Delivery System.